Examining the factors influencing young individuals willingness to donate online through TikTok - Novrin, Khairani Azizah (Alkasb: Journal of Islamic Economics, 2025)
Indonesia has the largest TikTok user base in the world, with 157.6 million users, making it a key platform for marketing and social initiatives, including charitable donations. However, there is limited understanding of the factors influencing young people's behavioral intentions when donating via TikTok. This research aims to explore the behavioral intentions of young individuals in deciding to donate through TikTok, with a focus on emotional drivers. The findings are expected to help zakat and other charitable institutions optimize their donation campaigns on the platform. The study employs a qualitative approach, utilizing questionnaires distributed primarily to young respondents to assess their donation behavior and motivations on TikTok. The results indicate that emotional factors play a significant role in shaping young people's decisions to donate online. These insights can guide institutions in designing more effective TikTok campaigns to enhance youth participation in social welfare initiatives.